On the Importance of Processing Conditions for the Nutritional Characteristics of Homogenized Composite Meals Intended for Infants - Östman, Elin; Forslund, Anna; Tareke, Eden; Björck, Inger (Nutrients, 2016)
The nutritional quality of infant food is an important consideration in the effort to prevent a further increase in the rate of childhood obesity. We hypothesized that the canning of composite infant meals would lead to elevated contents of carboxymethyl-lysine (CML) and favor high glycemic and insulinemic responses compared with milder heat treatment conditions. We have compared composite infant pasta Bolognese meals that were either conventionally canned (CANPBol), or prepared by microwave cooking (MWPBol). A meal where the pasta and Bolognese sauce were separate during microwave cooking (MWP_CANBol) was also included. The infant meals were tested at breakfast in healthy adults using white wheat bread (WWB) as reference. A standardized lunch meal was served at 240 min and blood was collected from fasting to 360 min after breakfast. The 2-h glucose response (iAUC) was lower following the test meals than with WWB. The insulin response was lower after the MWP_CANBol (−47%, p = 0.0000) but markedly higher after CANPBol (+40%, p = 0.0019), compared with WWB. A combined measure of the glucose and insulin responses (ISIcomposite) revealed that MWP_CANBol resulted in 94% better insulin sensitivity than CANPBol. Additionally, the separate processing of the meal components in MWP_CANBol resulted in 39% lower CML levels than the CANPBol. It was therefore concluded that intake of commercially canned composite infant meals leads to reduced postprandial insulin sensitivity and increased exposure to oxidative stress promoting agents.